Complementary Feeding and Diarrhea and Respiratory Infection Among HIV-Exposed Tanzanian Infants. (1st March 2017) - Kamenju, Pili; Liu, Enju; Hertzmark, Ellen; Spiegelman, Donna; Kisenge, Rodrick R.; Kupka, Roland; Aboud, Said; Manji, Karim; Duggan, Christopher; Fawzi, Wafaie W.
Abstract : Objective: To examine the association between complementary feeding and risks of diarrhea and acute respiratory infection (ARI) among HIV-exposed infants aged 6–24 months. Design: We prospectively used an Infant and Child Feeding Index (ICFI) to measure complementary feeding practices (breastfeeding status, food consistency, dietary diversity, food group frequency, and meal frequency). We determined the association of ICFI and each of its components with the risk of diarrhea and ARI. Generalized estimating equations were used to estimate the relative risks for morbidity episodes. Setting: Dar es Salaam, Tanzania. Subjects: A total of 2092 HIV-exposed infants followed from 6 months of age to 24 months of age. Results: The ICFI score ranged from 0 to 9; the median score was 6 (interquartile range = 4–7). Low ICFI scores were likely associated with increased risk of dysentery [low vs. high tertile risk ratio (RR): 1.40; 95% confidence interval (CI): 0.93 to 2.10; P for trend = 0.02] and respiratory infection (low vs. high tertile RR: 1.16; 95% CI: 0.96 to 1.41; P for trend = 0.01). Low dietary diversity scores were likely associated with higher risk of dysentery (low vs. high tertile RR: 1.47; 95% CI: 0.92 to 2.35; P for trend = 0.03) and respiratory infection (low vs. high tertile RR: 1.41; 95% CI: 1.13 to 1.76; P for trend = 0.01). Low food consistency scores were associated with higher risk of respiratory infection (RR: 1.77; 95% CI: 1.40 to 2.26; P < 0.01). Conclusions: In this setting, low ICFI, dietary diversity, and food consistency scores were likely associated with increased risk of diarrhea and ARI among HIV-exposed infants.